ADVANCED FOREIGN EXPERIENCES IN INCREASING COMPETITIVENESS OF ENTERPRISES BASED ON THE IMPLEMENTATION OF A QUALITY SYSTEM (ISO, TQM AND OTHERS) - Bustonov Komiljon Kumakovich; Ikromov Sherali Adizovich (Web of Journals Publishing, 2025)
The article discusses the advanced foreign experience of increasing competitiveness based on the implementation of a quality system in increasing the competitiveness of enterprises. Also used are a systemic and comprehensive approach, analysis and synthesis, induction and deduction, the method of observing a monographic description, grouping and other methods.
Keywords: Deduction, induction, innovation, index, intellectual activity, effective schemes, Global Innovation Index, analysis and synthesis.